Design and theoretical study of a polarization-insensitive multiband terahertz metamaterial bandpass filter - 李海鹏;付文悦;沈晓鹏;韩奎;王伟华 (Chinese physics B, 2017)
We report the design of a novel multiband metamaterial bandpass filter （BPF） in the terahertz （THz）-wave region. The designed BPF is composed of a metal-dielectric-metal sandwiched structure with three nested rings on the top surface and a cross structure on the bottom surface. Full-wave simulation results show that the designed BPF has three transmission peaks at frequencies of 0.42, 1.27, and 1.86 THz with transmission rates of-0.87,-1.85, and-1.83 dB, respectively. Multi-reflection interference theory is introduced to explain the transmission mechanism of the designed triple-band BPF. The theoretical transmission spectrum is in good agreement with the full-wave simulated results. The designed BPF can maintain a stable performance as the incident angle varies from 0 to 30 for both transverse electric and transverse magnetic polarizations of the incident wave. The designed BPF can be potentially used in THz devices due to its multiband transmissions, polarization insensitivity, and stable wide-angle response in the THz region.